Hubungan Religiusitas dan Motivasi menjadi Relawan dengan Perilaku Prososial Anglican Community Center Batam - Sukamti, Sukamti; Suroso, Suroso; Saragih, Sahat (Faculty of Psychology, Universitas 17 Agustus 1945 Surabaya, 2019)
AbstrackAnglican Community Center Batam is a community of social volunteers who gives their time, energy and funds to help people who are in difficulities. The illegal house (ruli) community of Baloi Kolam Batam is known as a community where the people live in difficulties and have violence, alcoholic, infidelity and low prosocial behaviors. Anglican Community Centre volunteers give assistance through medical programs, food distribution, reading and writing tuition and character education at ruli Baloi Kolam. Everything is given free of charge. The purpose of this study is to determine the correclation of religiosity and motivation to be volunteers with prosocial behavior at Batam's Anglican Community Center volunteers. This study involves 66 volunteers from Batam's Anglican Community Center. The research instrument used is the scale of prosocial behavior, religiosity and motivation to be volunteers. This study uses multiple regression analysis techniques that are processed with the SPSS version 20. The results of the study show (1) religiosity has a very significant correlation with prosocial behavior with a calculated t value of 2.781 and siginification of 0.007 (p<0.01); (2) motivation to be volunteers has a very significant correlation with a value of t count of 3.835 and a significance of 0.000 (p<0.01); (3) religiosity and motivation to be volunteers have a very significant correlation simultaneously with prosocial behavior with a F value of 20.813 and a significance of 0.000 (p<0.01). The implication of this research is that volunteers at Anglican Community Center Batam need to maintain and further improve religiosity as a means to maintain motivation to be volunteers so that they increase their prosocial behavior.Keywords: Religiosity, Motivation To Be Volunteers and Prosocial Behavior